Inovasi Produk dan Pemasaran Digital untuk Meningkatkan Daya Saing UMKM Hampers di Desa Sembung - Utama, Agung; Wijaya, Tony; Wardana; Ghaffar, Alfian Abdul; Achmadi, Caesar Rosyad (IKIP PGRI Bojonegoro, 2025)
ABSTRACT Sembung Village in Wedi District, Klaten Regency, has strong potential to develop as a center for hampers-based Micro, Small, and Medium Enterprises (MSMEs). Several existing wedding equipment rental businesses have created an initial market ecosystem for hamper products and souvenirs. However, this potential has not yet been supported by adequate product innovation and digital marketing capabilities. Local MSME actors still face obstacles in designing creative hampers, applying proper packaging techniques, developing branding, and utilizing digital platforms, which limits their competitiveness and keeps them dependent on conventional marketing. This community engagement program aims to enhance the competitiveness of MSMEs in Sembung Village through product innovation training and digital marketing strategies. The methods used include lectures, demonstrations, hands-on practice, and intensive mentoring on hamper design, product photography, storytelling, and promotion through social media and online marketplaces. The evaluation involved pre-tests, post-tests, observation, and participant feedback. The results demonstrate a significant improvement in participants’ understanding of digital marketing, promotional content development, and packaging creativity, with an average increase of over 100 percent. Participants successfully produced new hamper designs, created digital catalogs, and managed online business accounts. This program has proven effective in strengthening creative economy-based MSMEs and expanding their market opportunities through digitalization. Keywords: digital marketing, product innovation, MSMEs, empowerment, Hampers ABSTRAK Desa Sembung di Kecamatan Wedi, Kabupaten Klaten, memiliki potensi kuat untuk berkembang sebagai sentra UMKM hampers karena telah terdapat beberapa usaha sewa perlengkapan dan alat penikahan yang menjadi ekosistem awal tumbuhnya permintaan produk hantaran dan suvenir. Namun, potensi tersebut belum diikuti oleh kemampuan inovasi produk dan pemasaran digital yang memadai. Pelaku UMKM masih menghadapi kendala dalam kreativitas desain hampers, teknik pengemasan, branding, dan pemanfaatan media digital sehingga daya saing produk masih terbatas pada pemasaran konvensional. Kegiatan pengabdian ini bertujuan meningkatkan daya saing UMKM Desa Sembung melalui pelatihan inovasi produk dan strategi pemasaran digital. Metode yang digunakan mencakup ceramah, demonstrasi, praktik langsung, serta pendampingan intensif dalam desain hampers, fotografi produk, storytelling, dan pemasaran berbasis media sosial maupun marketplace. Evaluasi dilakukan melalui pre–test, post–test, observasi, dan umpan balik peserta. Hasil menunjukkan peningkatan signifikan pada pemahaman peserta mengenai digital marketing, pembuatan konten promosi, dan kreativitas pengemasan dengan rata-rata peningkatan kompetensi di atas 100%. Peserta mampu menghasilkan desain hampers baru, membuat katalog digital, serta membangun akun bisnis daring. Kegiatan ini terbukti efektif mendorong kemandirian UMKM berbasis ekonomi kreatif dan membuka peluang perluasan pasar melalui digitalisasi. Kata kunci: digital marketing, inovasi produk, UMKM, pemberdayaan, Hampers